Dynamics Research of the 3-TPT Parallel Mechanism based on Kane Equation - Zhao Xueyang; Zhao Henghua; Yang Shibin; Mu Hongping (Jixie chuandong)
Taking the 3- TPT parallel mechanism as study object,the dynamics of the 3- TPT parallel mechanism is studied. A formulation based on Kane equation is educed for the dynamics of the Stewart platform manipulator from the kinematics analysis of the model. The relation between velocity and acceleration of platform and driving bar are analyzed. Then the dynamics equations of the 3- TPT parallel mechanism is derived with the help of Kane equation. Finally,the simulation analysis of relationship between the driving force and time is carried outs by MATLAB software. The result show that,the driving force of 3- TPT parallel mechanism is changed periodically,and mutation in the acceleration and deceleration phases.